Report of the Working Party on Hybridoma-Derived Monoclonal Antibodies to Platelets - Coller, Barry S (Thrombosis and Haemostasis, 1984)
A registry of 24 hybridoma-derived monoclonal antibodies to platelets is reported along with the deliberations of the Working Party on criteria for inclusion into the registry and nomenclature.
Keywords: Platelets; Monoclonal antibodies; Hybridomas; Registry